UNDERSTANDING ENTREPRENEURIAL INTENTION IN THE DIGITAL ECONOMY: THE IMPACT OF LITERACY SKILLS AND LOCUS OF CONTROL - Siska, Siska; Asriati, Nuraini; Syahrudin, Husni; Witarsa, Witarsa; Budiman, Jumardi (Universitas Tanjungpura, 2025)
To foster interest in entrepreneurship, it is necessary to first know the factors that influence the emergence of this interest. One of the things that can influence interest in entrepreneurship is good digital literacy and having self-confidence or lack of control. This research aims to determine the magnitude of the influence of digital economic literacy and locus of control on the entrepreneurial interest of FKIP students at Tanjungpura University. The research method used is multiple linear regression analysis in quantitative form, while the source of data obtained is through questionnaires carried out by economic education students from the 2020, 2021 and 2022 classes for Regular A and PPAPK classes and the data was obtained from the results of distributing questionnaires. using google forms. The sample used was 111 economic education students from the classes of 2020, 2021, and 2022. The results of this research show that: 1) Economic digital literacy has a significant or positive influence on interest in entrepreneurship with a t value of 10,156 > t tabel 1,982, 2) Locus of Control has a significant influence on interest entrepreneurship with a t value of 11,475 > t tabel 1,982, 3) Economic digital literacy and locus of control have a direct influence on interest in entrepreneurship among economic education students with a f value of 82,487 > f tabel 3,08